Permissibility and infringement. The judicialization of “sex change” during the civil-military dictatorship in Chile (Clepsidra - Interdisciplinary Journal of Memory Studies, 2020)
This article analyzes the politics of exceptionalism that emerged within fragmentary and “permissive” regulations that enabledthe judicialization of “sex change” and that resulted in the infringement of trans people’s lives by the institutions of the ChileanState, both during the dictatorship and the post-dictatorial period. The article aims to identify different forms of violence thatwere developed and carried out by State institutions in the 1980s, when Chile was under a dictatorial regime that coexisted withthe consolidation of a neoliberal governmentality. The present text proposes to consider how trans historicities disturb the cleardistinction between dictatorship and post dictatorship, compelling us to confront different ways of approaching the past, disturbinglinear historical narratives.
Keywords: â€œsex changeâ€, dictatorship, judicialization, institutional violence